2022
DOI: 10.1002/adma.202208698
|View full text |Cite
|
Sign up to set email alerts
|

A Switchable One‐Compound Diode

Abstract: A diode requires the combination of p‐ and n‐type semiconductors or at least the defined formation of such areas within a given compound. This is a prerequisite for any IT application, energy conversion technology, and electronic semiconductor devices. Since the discovery of the pnp‐switchable compound Ag10Te4Br3 in 2009, it is in principle possible to fabricate a diode from a single material without adjusting the semiconduction type by a defined doping level. Often a structural phase transition accompanied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
6
0
1
Order By: Relevance
“…Thermal conductivity calculated according to eq amounts to 0.31 W m –1 K –1 at 303 K and 0.50 W m –1 K –1 at 573 K; the results are shown in Figure e. Those quite low values are around 1 order of magnitude lower than in the bulk binary copper telluride Cu 2 Te (2–4 W m –1 K –1 at RT) and still half of the values for Cu 2 Se (around 1 W m –1 K –1 at RT and 400 K), , whereas they are quite similar to the ones observed for coinage metal polytelluride halides like Ag 10 Te 4 Br 3 or Ag 18 Cu 3 Te 11 Cl 3 (0.14–0.43 W m –1 K –1 ) and Cu 9.1 Te 4 Cl 3 (0.4–0.6 W m –1 K –1 ) . Taking the only stable values for annealed samples into account, the thermal conductivity reaches values between 0.7 and 1 W m –1 K –1 .…”
Section: Resultssupporting
confidence: 58%
“…Thermal conductivity calculated according to eq amounts to 0.31 W m –1 K –1 at 303 K and 0.50 W m –1 K –1 at 573 K; the results are shown in Figure e. Those quite low values are around 1 order of magnitude lower than in the bulk binary copper telluride Cu 2 Te (2–4 W m –1 K –1 at RT) and still half of the values for Cu 2 Se (around 1 W m –1 K –1 at RT and 400 K), , whereas they are quite similar to the ones observed for coinage metal polytelluride halides like Ag 10 Te 4 Br 3 or Ag 18 Cu 3 Te 11 Cl 3 (0.14–0.43 W m –1 K –1 ) and Cu 9.1 Te 4 Cl 3 (0.4–0.6 W m –1 K –1 ) . Taking the only stable values for annealed samples into account, the thermal conductivity reaches values between 0.7 and 1 W m –1 K –1 .…”
Section: Resultssupporting
confidence: 58%
“…With the realization of one-compound diode devices, like in the case of Ag 18 Cu 3 Te 11 Cl 3 , it has been shown that a diode can be generated on demand and position-independently. [14] Once one-compound diodes are transferred into the aforementioned processes, this aspect may increase the flexibility of the device architecture drastically. With pnp-switching materials applied as one-compound diodes, more versatility can be achieved not only concerning the position, but in principle also in the direction of current flow.…”
Section: Introductionmentioning
confidence: 99%
“…Using Ag 18 Cu 3 Te 11 Cl 3 , the first one-compound diode device was prepared and the diode formation and performance for this system were reported. [14] Another interesting attempt to fabricate a diode via pn-junctions was the realization of an organic single molecule diode. [15] Here, weakly coupled π-systems with donor and acceptor units that are attached to a rod can result in a diode-like U/I curve at 30 K.…”
mentioning
confidence: 99%
“…= 7.07%) is the preferred isotope over 123 Te (γ = −7.06 × 10 7 rad s –1 T –1 ; Ξ = 26.17%, N.A. = 0.89%) due to its higher natural abundance and frequency ratio, and yields sharp NMR line shapes with excellent resolution over a large chemical shift window of ∼5000 ppm that is sensitive to different electronic structures and Te oxidation states in various organo- and inorganic tellurium compounds. …”
Section: Resultsmentioning
confidence: 99%